Supramolecular association involving anion–π interactions in Cu(II) coordination solids: Experimental and theoretical studies. (1st September 2018) - Dutta, Debajit; Chetry, Sanjib; Gogoi, Anshuman; Choudhury, Bula; Guha, Ankur K.; Bhattacharyya, Manjit K.
Graphical abstract: Two new Cu(II) coordination solids based on N- and O-donor ligands, viz. [Cu2 (µ- tp )( phen )4 ](NO3 )2 ·2H2 O (1 ) and [Cu( pa )2 (NO3 )(H2 O)]NO3 ·H2 O (2 ), have been successfully synthesized and characterized. The single crystal XRD structures reveal that weak anion–π, π–π along with hydrogen bonding interactions form 2D networks in the complexes. Theoretical investigations have been carried out for the supramolecular contacts and the calculations reveal that in addition to electrostatics, induction and dispersion components are also significant towards stabilization of the supramolecular interactions for the complexes. Abstract: Two new coordination solids, [Cu2 (µ- tp )( phen )4 ](NO3 )2 ·2H2 O (1 ) and [Cu( pa )2 (NO3 )(H2 O)]NO3 ·H2 O (2 ) ( phen  = 1, 10-phenanthroline, tp  = terephthalate, pa  = picolinamide), were synthesized from purely aqueous media and characterized using elemental analysis, spectroscopic methods (IR, UV–Vis–NIR and ESR) and the single crystal X-ray diffraction technique. In the crystal structures of 1 and 2, supramolecular networks have been built up involving associations with OH⋯O, CH⋯O and π–π stacking interactions. In addition, both compounds show anion–π interactions involving non-coordinated nitrate ions and the aromatic rings of the complexes. The nitrate anions and non-coordinated water molecules in both compounds, with the graph set representation R 2 4 ( 8 ), act as cross-links between symmetry related cationic chains via hydrogen bonding interactions to form 2D layered supramolecular architectures. Theoretical investigations have been carried out on all the supramolecular contacts, including anion–π interactions, taking into account the particular position of the anion toward the aromatic ring observed in the crystal structures. Calculations reveal that in addition to the electrostatics, induction and dispersion components are also significant towards the stabilization of the supramolecular interactions. The phase purity and thermal stability of the compounds were verified by powder X-ray diffraction (PXRD) and thermogravimetric (TG) analyses, respectively. The microbial activities have been investigated for compound 1 .